2010
DOI: 10.1097/scs.0b013e3181d7f2b0
|View full text |Cite
|
Sign up to set email alerts
|

Mandibular Osteomyelitis and Fracture in a Patient With Pyknodysostosis

Abstract: Pyknodysostosis is a rare, recessive, hereditary, autosomal disease belonging to the group of bone dysplasias. Complications such as osteomyelitis and fractures of the mandible are not uncommon and appear in the most varied forms. We report a case of chronic osteomyelitis with subsequent mandible fracture, which was successfully treated with the use of a reconstruction plate and antibiotic therapy. This article outlines the clinical and radiographic characteristics of this condition based on the clinical case … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 18 publications
0
18
0
Order By: Relevance
“…This condition may determine weakening of the mandibular bone and subsequent pathological fractures. Several predisposing diseases may be associated with osteomyelitis, such as diabetes, osteogenesis imperfecta, and pyknodysostosis (Table ).…”
Section: Mandibular Fractures Associated With Osteomyelitismentioning
confidence: 99%
See 2 more Smart Citations
“…This condition may determine weakening of the mandibular bone and subsequent pathological fractures. Several predisposing diseases may be associated with osteomyelitis, such as diabetes, osteogenesis imperfecta, and pyknodysostosis (Table ).…”
Section: Mandibular Fractures Associated With Osteomyelitismentioning
confidence: 99%
“…Mean age of patients included in this category is 50.5 years, ranging between 1 and 75 years ( Table 5) The incidence of fractures associated with osteomyelitis is higher in male patients with a general male-to-female ratio of 1.5:1. The most frequently involved site is mandibular angle (3,5,(71)(72)(73), followed by mandibular body (3,68,69,74).…”
Section: Mandibular Fractures Associated With Osteomyelitismentioning
confidence: 99%
See 1 more Smart Citation
“…They were able to achieve bony fusion at 13 months. Frota et al [11] reported a case in which a 45-year-old patient presented with osteomyelitis and a pathological fracture in the mandibular body and was successfully treated with a reconstruction plate and antibiotic therapy. Although at 36-month follow-up this more conservative therapy provided an alternative solution to a bone graft, due to our patient's significant atrophy of the mandible this did not appear to be a feasible solution to provide bone union.…”
Section: Discussionmentioning
confidence: 98%
“…The typical features of pycnodysostosis include short stature, an increase in the bone density of long bones, pathological fractures with poor healing, stubby hands and feet with dystrophic nails, and typical craniofacial features (Xue et al, 2011). Here, we summarized the typical craniofacial features of pycnodysostosis in 135 reported cases (Table 1) (Arman et al, 2014;Balaji et al, 2014;Berenguer et al, 2012;Caracas et al, 2012;Cortisse et al, 2012;Della Marca et al, 2012;Farronato et al, 2014;Girbal et al, 2013;Huang et al, 2015;Kamak et al, 2012;Kshirsagar et al, 2012;Kumar, 2014;Kyung and Horton, 2015;Ortegosa et al, 2014;Ozdemir et al, 2013;Pangrazio et al, 2014;Puri et al, 2013;Raposo-Amaral et al, 2013;Rohit et al, 2015;Singh et al, 2015;Singh and Sambandam, 2014;Tinsa et al, 2014;Utokpat et al, 2013;Xue et al, 2015;Ainola et al, 2008;Alibhai et al, 1999;Alves Pereira et al, 2008;Bathi and Masur, 2000;Bertola et al, 2010;Chavassieux et al, 2008;Chen et al, 2007;Dimitrakopoulos et al, 2007;Fonteles et al, 2007;Fratzl-Zelman et al, 2004;Frota et al, 2010;…”
Section: Oral and Maxillofacial Abnormities In Patients With Pycnodysmentioning
confidence: 96%